2013
DOI: 10.1002/pssr.201308111
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐transfer‐induced doping at an electron donor (α‐sexithiophene)/acceptor (C60) interface and mobility improvement

Abstract: We studied various aspects relating to surface charge‐transfer‐induced doping at an organic/organic interface using in situ electrical measurements with a field‐effect transistor (FET) during the formation of the electron donor/acceptor interface. Adsorption of the electron‐accepting molecules (C60) on top of the electron donating molecules (α‐6T) led to an increase in the FET hole mobility in an α‐6T film. Under illumination, the FET hole mobility in the α‐6T film with C60 deposition was significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Oligothiophenes (oT), polythiophene (nT), and their derivatives are conjugated molecular systems that exhibit narrow and tunable optical band gaps and high conductivity. Because of these outstanding molecular properties, they have been widely used as functional materials in organic electronic devices such as field-effect transistors, organic light-emitting diodes, , organic photovoltaic devices (OPVs), , and bioelectronics. , As a derivative of nT, poly­(3-hexylthiophene-2,5-diyl) (P3HT) is a widely used donor material blended with phenyl-C 61 -butyric acid methyl ester in bulk heterojunction (BHJ) OPVs. , As a small molecule alternative to polymer-based BHJs, sexithiophene (6T)-based BHJs are considered to be more structurally tunable. Due to shallow (i.e., not far in energy below the vacuum level) highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels, oTs and nTs are most commonly used as electron donors in organic electronic devices. Previous studies have shown that multiple oxidation states are accessible for the oligothiophenes and their derivatives via electrochemical , and chemical oxidation; however, there have been no instances of oT reduction chemistry reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Oligothiophenes (oT), polythiophene (nT), and their derivatives are conjugated molecular systems that exhibit narrow and tunable optical band gaps and high conductivity. Because of these outstanding molecular properties, they have been widely used as functional materials in organic electronic devices such as field-effect transistors, organic light-emitting diodes, , organic photovoltaic devices (OPVs), , and bioelectronics. , As a derivative of nT, poly­(3-hexylthiophene-2,5-diyl) (P3HT) is a widely used donor material blended with phenyl-C 61 -butyric acid methyl ester in bulk heterojunction (BHJ) OPVs. , As a small molecule alternative to polymer-based BHJs, sexithiophene (6T)-based BHJs are considered to be more structurally tunable. Due to shallow (i.e., not far in energy below the vacuum level) highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels, oTs and nTs are most commonly used as electron donors in organic electronic devices. Previous studies have shown that multiple oxidation states are accessible for the oligothiophenes and their derivatives via electrochemical , and chemical oxidation; however, there have been no instances of oT reduction chemistry reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…While this assumption is almost certainly true for the studies at 120 K, it may be less true at room temperature. However, this is an assumption that has been commonly made for deposition of similarly reactive metals on OT and P3HT films in past work; ,, , therefore, we use it here. QCM-reported mass thicknesses for the metals were converted into equivalent metal monolayers using the approach reported by Bebensee , using proper metal lattice constants ( a Ag = 0.40853 nm, a Mg = 0.32094 nm, a Al = 0.40495 nm, a Ca = 0.35884 nm) assuming the close-packed (111) structure for the FCC metals Ag, Al, and Ca and the (0001) structure for the HCP metal Mg. Metal coverages are reported throughout in terms of equivalent monolayers.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Following our recent spectroscopic studies of metal–organic interfacial molecular processes between Ag, Al, Mg, and Ca and oligothiophenes, including 2,2′:5′,2″-terthiophene (α-3T) and α-sexithiophene (α-6T), this work describes estimation of both the penetration depth of different metals as well as the impact depth of the reaction chemistry of these oliogthiophenes (OTs) using spectroscopic methods. These two oligothiophenes have very similar spectroscopic and materials properties and both are well-accepted as models for polythiophene-based active layer materials. Here, Raman spectroscopy is combined with depth sensitive, angle-dependent X-ray photoelectron spectroscopy (XPS) to explore OT reduction chemistry as a function of metal coverage.…”
Section: Introductionmentioning
confidence: 99%